EVALUATION OF THE DRUG-FREE VILLAGE PROGRAM IN KEDIRI CITY - Sari, Faradilla Indah Oktavia; Tama, Tika Dwi; Adi, Sapto; Ulfah, Nurnaningsih Herya (Jurnal Ilmu Kesehatan Masyarakat, 2025)
Cases of drug abuse and illicit trafficking are increasingly worrying. Drug users continue to increase. Data shows that urban areas are more prone to drug abuse and illicit trafficking than rural areas. The Drug-Free Village Program has been implemented in Kediri City since 2020. This program can help reduce drug vulnerability in the Kediri City area. In addition, it can also reduce the number of drug abuse in Kediri City. The purpose of this study was to evaluate the Drug-Free Village Program in Kediri City from the aspects of input, process, and output. This research is a qualitative study with a case study approach. The determination of the research location is based on the Circular Letter of the National Narcotics Agency of the Republic of Indonesia concerning Data on Drug-Prone Areas of the Year. The data collection technique used in this study was in-depth interviews. The selection of informants in this study used purposive sampling techniques. The research instrument used interview guidelines and achievement sheets for the success assessment indicators of the Drug-Free Village Program. The results of the study showed that the Drug-Free Village Program in Dandangan Village and Ngampel Village had achieved the success assessment indicators for the Drug-Free Village. However, community participation in providing information regarding drug abuse and illicit trafficking has not been optimal, with some residents still reluctant to report cases. The Drug-Free Village Program must be sustainable to eradicate Indonesia’s drug abuse and illicit trafficking problems.